How Loan Distribution and Credit Troubled in Fostered Partners can be Done? Case Study: CSR Fund from PT. Bukit Asam Tbk. Tanjung Enim, South Sumatra, Indonesia - Riwukore, Jefirstson Richset (Institut Agama Islam Negeri Kendari, 2021)
This research aims to determine the Corporate Social Responsibility (CSR) partnership program implemented by State-Owned Enterprises, BUMN, namely PT. Bukit Asam, Tbk, Tanjung Enim, South Sumatra, as a form of concern for the community of small business actors by providing business capital loan assistance. Credit extension services cannot be separated from the risks that occur, such as non-performing loans. Non-performing loans that happened in PT. Bukit Asam Tanjung Enim South Sumatra, namely small business actors as fostered partners experienced a disaster, went bankrupt and fled, or business owners died. This research method uses descriptive qualitative analysis, administrative procedures for granting credit, analysing systems for giving credit assessment, monitoring credit, calculating the level of the collectibility of non-performing loans, and analysing efforts to rescue non-performing loans. The analysis results show that in 2015 to 2017 and 2018, the category of non-performing loans dominates from other categories. In 2015, 2017,2018 and 2019, the collectability in the current category experienced an increase from 1.8%, up 8.6%, up 35.40% and up to 749.87%. The percentage of loan collectibility obtained shows the amount of non-performing loans in 2015 to 2017, 2018 and 2019 has fluctuated and tends to decrease, from 78.11% to 88.74%. Reduced to 60.45% and fell to 27.58%. This finding shows that there are efforts to improve credit performance to have no problem with credit. It is recommended to CSR managers of PT. Bukit Asam, Tbk. Agra must pay attention to the level of business turnover and the provision of collateral in anticipation of bad credit and for existing lousy credit to be rescheduled or reconditioned for loan arrears or can submit evidence of problematic receivables or write-off of accounts receivable if the conditions are not collectable.